Determination of kinetic regularities of the process of drying perlite by radiation method - Novokhat O. A.; Vozniuk V. T.; Hritsiuk H.I.; Lysii V. (Журнал інженерних наук)
The actual methods of perlite drying are established. The radiation method of perlite drying is offered. A description of an experimental installation for drying perlite by the radiation method is given. The kinetic regularities of this method are established. Graphical dependences of moisture content on drying time, perlite surface temperature on drying time, and drying speed of perlite on drying time are described. The influence of the initial moisture content of perlite, the value of the heat flux density from the infrared emitter, the thickness of the perlite layer, and the value of the perlite fraction were determined. The analysis on the resulted graphic dependences is made. A drying installation with a combined drying method is proposed. The general conclusions concerning the expediency of a radiation method of drying perlite are made.